2015
DOI: 10.1111/jsbm.12184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organizational Form and Customer Type on Online Customer Satisfaction Ratings

Abstract: International audienceIn this paper, we explore the impact of the organizational form (company‐owned versus franchised) and the type of customer (nonbusiness versus business) on online consumer‐generated satisfaction ratings in the hotel industry. Our empirical study deals with 6,348 TripAdvisor reviews regarding stays at one of 134 hotels of a plural form chain located in a Western European country. Our main finding reveals that the type of customer moderates the relationship between organizational form and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 86 publications
(172 reference statements)
1
16
0
Order By: Relevance
“…Value remains the most prominent variable in order to increase the occupancy percentage. Previous research has supported the importance of cleanliness of franchise properties over that of chain-managed properties (Lawrence & Perrigot, 2015); the findings of this study are consistent with those of past studies.…”
Section: Franchisedsupporting
confidence: 92%
See 4 more Smart Citations
“…Value remains the most prominent variable in order to increase the occupancy percentage. Previous research has supported the importance of cleanliness of franchise properties over that of chain-managed properties (Lawrence & Perrigot, 2015); the findings of this study are consistent with those of past studies.…”
Section: Franchisedsupporting
confidence: 92%
“…Bilim and Basoda (2014) found that while consumers pay attention to many different issues, services and related areas are considered to be the prevalent. Lawrence and Perrigot (2015) found that customers were more satisfied with the level of service received at companyowned hotels over that of franchise hotels. The various service components that make customer satisfied may also make them dissatisfied if they are not provided or are found to be delivered inadequately (Berezina et al, 2016).…”
Section: Cleanlinessmentioning
confidence: 97%
See 3 more Smart Citations